Thylakoid-bound ascorbate peroxidase mutant exhibits impaired electron transport and photosynthetic activity - Danna, Cristian H. (2003)
In chloroplasts, stromal and thylakoid-bound ascorbate peroxidases (tAPX) play a major role in the removal of H2O2 produced during photosynthesis. Here, we report that hexaploid wheat (Triticum aestivum) expresses three homeologous tAPX genes (TaAPX-6A, TaAPX-6B, and TaAPX-6D) mapping on group-6 chromosomes. The tAPX activity of a mutant line lacking TaAPX-6B was 40% lower than that of the wild type. When grown at high-light intensity photosystem II electron transfer, photosynthetic activity and biomass accumulation were significantly reduced in this mutant, suggesting that tAPX activity is essential for photosynthesis. Despite the reduced tAPX activity, mutant plants did not exhibit oxidative damage probably due to the reduced photochemical activity. This might be the result of a compensating mechanism to prevent oxidative damage having as a consequence a decrease in growth of the tAPX mutant plants.